Meningomielocele e seu manejo na genética pediátrica: uma revisão de tema de seus aspectos biomédicos e psicossociais - Luan Nogueira Duarte; Lia Nogueira Duarte; José Humberto Sousa Morais Júnior; Fabricia Maria de Souza Saraiva; Amanda Kely Nogueira Oliveira; Wallace William da Silva Meireles; Erlane Marques Ribeiro (Residência Pediátrica)
OBJECTIVES: This study aims to analyze myelomeningocele as a prevalent congenital anomaly and its general pathological aspects, while highlighting potentially protective measures and the importance of multiprofessional care. METHODS: A theme review was conducted, encompassing studies on myelomeningocele and spina bifida. Epidemiological data, pathological aspects, and primary prevention measures such as the consumption of folic acid and vitamin B12 were analyzed, interpreted, and compiled. RESULTS: Myelomeningocele is the most common manifestation of spina bifida, resulting from the incomplete closure of the neural tube. It can be influenced by genetic and environmental factors. The consumption of folic acid and vitamin B12 has been associated with a reduced risk of congenital malformations, including myelomeningocele. However, these measures do not completely eliminate cases. CONCLUSION: Primary prevention of myelomeningocele involves raising awareness about the importance of consuming folic acid and vitamin B12. However, it is essential to recognize that these measures alone are not sufficient to eradicate the disease entirely. Multiprofessional care plays a crucial role in improving patients quality of life through a longitudinal and continuous approach within care networks.